2008
DOI: 10.1139/x08-018
|View full text |Cite
|
Sign up to set email alerts
|

Competitive success of natural oak regeneration in clearcuts during the stem exclusion stage

Abstract: We sampled dominant and codominant regeneration on 70 clearcuts, 21–35 years old, on the Hoosier National Forest in southern Indiana, USA, to evaluate influence of site variables on the competitive success of natural oak ( Quercus L.) over time. Collected data was compared with data collected on these same sites 20 years prior. Regression tree analysis indicated aspect, natural region, and oak abundance in preharvest stands had the greatest influence on competitive success (relative density, RD) of oak species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…removed approximately 20 years prior (Morrissey et al 2009). Harvest volumes from clearcuts (Morrissey et al 2008) indicated that species composition was sufficiently similar to reference stands of Van Kley (1993). At least 45% of oak regeneration was clearly identified as stump sprouts (Morrissey et al 2008), but it is estimated that the actual percentage was higher.…”
Section: Study Areamentioning
confidence: 64%
See 2 more Smart Citations
“…removed approximately 20 years prior (Morrissey et al 2009). Harvest volumes from clearcuts (Morrissey et al 2008) indicated that species composition was sufficiently similar to reference stands of Van Kley (1993). At least 45% of oak regeneration was clearly identified as stump sprouts (Morrissey et al 2008), but it is estimated that the actual percentage was higher.…”
Section: Study Areamentioning
confidence: 64%
“…In the Missouri Ozark Highlands, Sasseen and Muzika (2004) indicated that fire disturbances may override effects of site that typically control succession in the region, suggesting successional pathways may vary across ELTPs as a result of different disturbances. Morrissey et al (2008) observed that Quercus species relative density increased between 1986 and 2004 in relation to site variables including ecological section, aspect, and, to a lesser degree, slope position. It was proposed that Quercus species held a competitive advantage over many co-occurring species, notably site-sensitive species such as L. tulipifera and P. serotina, because of oaks' ability to better tolerate periods of water stress (autogenic) on more xeric sites (allogenic).…”
Section: Ecological Classification System Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Oak stump sprouts are highly competitive and often account for the majority of dominant oaks in the stem exclusion stage (Beck and Hooper, 1986;Gould et al, 2002;Morrissey et al, 2008), but not all oak stumps that result from harvesting produce sprouts (e.g., Johnson, 1977;Weigel et al, 2011), which is why emphasis is placed on development of large oak advance reproduction in the understory to sustain desired oak stocking in the future stand (Johnson et al, 2009). In general, the single-tree selection method is not recommended for oak regeneration (Johnson et al, 2009).…”
Section: Combining Fire and Regeneration Methodsmentioning
confidence: 99%
“…We cannot, however, speculate as to whether yellow poplar or any other species were common host species for grapevines at earlier stages of development. On these same sites, Morrissey et al (2008b) determined that neither yellow poplar nor black cherry showed significant reductions in relative density of dominant and co-dominant trees between the two sample periods, indicating that they remained competitive during that period despite grapevine competition. We speculate that as competition for light resources increased in developing canopies, grapevine densities decreased, perhaps as a result of their shade intolerance.…”
Section: Grapevine Dynamicsmentioning
confidence: 98%